2022
DOI: 10.33096/woph.v2i4.633
|View full text |Cite
|
Sign up to set email alerts
|

Faktor Yang Berhubungan Dengan Keluhan Musculoskeletal Disorders (MSDs) Pada Pegawai Yang Menggunakan Personal Komputer Di PT. PLN ULP Panakkukang Makassar Selatan

Abstract: Keluhan sistem musculoskeletal atau diistilahkan dengan keluhan musculoskeletal disorders (MSDs) adalah masalah ergonomi yang sering dijumpai ditempat kerja. Seperti pada pekerja yang menerima beban statis secara berulang dalam waktu yang lama dapat menyebabkan suatu keluhan pada bagian otot-otot skeletal, keluhan sangat ringan sampai dengan keluhan berat. Penelitian ini bertujuan mengetahui faktor yang berhubungan dengan keluhan MSDs pada Pegawai yang menggunkan Personal computer di PT PLN ULP Panakukkang Mak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
0
2
0
1
Order By: Relevance
“…This is supported by research by Helmina et al (2019), with the results of statistical analysis showing p = 0.014, showing a relationship between years of service and MSD. 22 Another study by Haq et al (2022) found a significant correlation between length of work per day and MSD complaints (p = 0.020). 23 The results of filling out the NBM 24 The complaints experienced by respondents may be caused by unnatural working postures away from the body's normal position, such as the back and neck being too flexed.…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation

Prevalence study of musculoskeletal disorders among bank workers

Gede Maheza Wiratama,
Made Hendra Satria Nugraha,
Ni Luh Nopi Andayani
2024
ptji
“…This is supported by research by Helmina et al (2019), with the results of statistical analysis showing p = 0.014, showing a relationship between years of service and MSD. 22 Another study by Haq et al (2022) found a significant correlation between length of work per day and MSD complaints (p = 0.020). 23 The results of filling out the NBM 24 The complaints experienced by respondents may be caused by unnatural working postures away from the body's normal position, such as the back and neck being too flexed.…”
Section: Methodsmentioning
confidence: 96%
“…22 Another study by Haq et al (2022) found a significant correlation between length of work per day and MSD complaints (p = 0.020). 23 The results of filling out the NBM 24 The complaints experienced by respondents may be caused by unnatural working postures away from the body's normal position, such as the back and neck being too flexed. If this position is held for a long time, the extensor muscles would work harder and fatigue.…”
Section: Methodsmentioning
confidence: 96%

Prevalence study of musculoskeletal disorders among bank workers

Gede Maheza Wiratama,
Made Hendra Satria Nugraha,
Ni Luh Nopi Andayani
2024
ptji
“…Terdapat ketidaksesuaian antara manusia dengan stasiun kerja yang digunakan sehingga dapat mengganggu aktivitas dan pekerjaannya serta jarang mengubah posisi kerja pada saat bekerja juga menjadi faktor pemicu adanya keluhan MSDs. Namun pada pegawai yang tidak mengalami keluhan disebabkan adanya inisiatif oleh pegawai itu sendiri seperti halnya pada salahsatu pegawai yang membawa bantal sandaran agar dapat dapat duduk dengan nyaman pada saat bekerja.Penelitian ini sejalan dengan penelitian yang dilakukan oleh Haq dkk (2021) dimana hasil uji statistik yang dilakukan oleh menggunakan uji chi-square diperoleh nilai p=0,084 (p>0,05) maka dapat disimpulkan bahwa sikap kerja tidak memiliki hubungan yang signifikan dengan keluhan musculoskeletal pada pegawai yang menggunakan komputer di PT PLN ULP Panakukang Makassar Selatan 17.…”
unclassified